Dermatological Aspects of COVID-19 - Sharma, Alina (Journal of Lumbini Medical College, 2020)
On 31 December 2019, Wuhan, the capital city of Hubei Province in China reported World Health Organization(WHO) about cases of pneumonia which were caused by a severe acute respiratorysyndrome coronavirus 2 (SARS-CoV-2) currently designated coronavirus disease (COVID-19). The infection rapidly spread throughout the world escalating the situation and WHO eventually declared COVID-19 as a global pandemic on 11 March 2020. It has already affected almost all aspects of health and society globally. With the current pandemic, dermatologists should be aware of dermatological aspects of SARS-CoV-2, its skin manifestations and general skin care.